2022
DOI: 10.1038/s41467-022-29767-7
|View full text |Cite
|
Sign up to set email alerts
|

Somatic whole genome dynamics of precancer in Barrett’s esophagus reveals features associated with disease progression

Abstract: While the genomes of normal tissues undergo dynamic changes over time, little is understood about the temporal-spatial dynamics of genomes in premalignant tissues that progress to cancer compared to those that remain cancer-free. Here we use whole genome sequencing to contrast genomic alterations in 427 longitudinal samples from 40 patients with stable Barrett’s esophagus compared to 40 Barrett’s patients who progressed to esophageal adenocarcinoma (ESAD). We show the same somatic mutational processes are acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 96 publications
4
25
0
Order By: Relevance
“…Our results strongly suggest that ecDNAs usually arise in regions of HGD in patients with Barrett’s oesophagus, and nearly always in the context of TP53 alteration. These results complement previous reports that found that TP53 alteration and altered copy number might drive the transition from metaplasia to dysplasia 10 , 13 , 14 , 45 , 46 , showing the cooperative nature of various genetic and epigenetic alterations, and suggesting that ecDNA formation represents a particularly potent driver of transformation and could be an opportunity for specific therapeutic intervention. Moreover, our analysis of a single patient across time supports and extends a report 46 suggesting that TP53 alteration results in polyploid tumours with multiple amplified or gained regions providing a reservoir for amplifying oncogenes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results strongly suggest that ecDNAs usually arise in regions of HGD in patients with Barrett’s oesophagus, and nearly always in the context of TP53 alteration. These results complement previous reports that found that TP53 alteration and altered copy number might drive the transition from metaplasia to dysplasia 10 , 13 , 14 , 45 , 46 , showing the cooperative nature of various genetic and epigenetic alterations, and suggesting that ecDNA formation represents a particularly potent driver of transformation and could be an opportunity for specific therapeutic intervention. Moreover, our analysis of a single patient across time supports and extends a report 46 suggesting that TP53 alteration results in polyploid tumours with multiple amplified or gained regions providing a reservoir for amplifying oncogenes.…”
Section: Discussionsupporting
confidence: 91%
“…4) to other genomic features, such as TP53. Disruption of TP53 enables genomic instability 13,14,28,29 , and we found a strong association in both FHCC and Cambridge samples between the TP53 alteration status (Methods, 'TP53 alteration analysis') and the presence of ecDNA (Extended Data Fig. 6a,b).…”
Section: Tp53 Alterations and Ecdna Formationmentioning
confidence: 73%
See 2 more Smart Citations
“…In the case of AAs, the homozygous SNP rs2814778 , which disrupts a binding site for the GATA1 erythroid transcription factor, resulting in a ACKR1 -null phenotype ( Figure 7A ), is known to cause low ANC ( 18 , 19 ). We used a case-control study ( 20 ) that included 80 patients with BE (n = 40 who progressed to EACs and 40 who did not [nonprogressors]); this cohort was selected from a larger case-cohort study within the Seattle Barrett’s Esophagus Program at the Fred Hutchinson Cancer Research Center. Germline data from this cohort were analyzed for the occurrence of 10 SNPs that increase or decrease the ANC, as determined in various studies in the United States ( Supplemental Methods ).…”
Section: Resultsmentioning
confidence: 99%